Analysis of Urban-Rural Coupling Coordination Based on Production,Living, and Ecological Functions in the Pearl River-Xijiang River Economic Belt - ZHANG Jianlong; LUO Jiangling; JIA Yanhong; XIE Ling (Renmin Zhujiang)
This paper studied the urban-rural system of the Pearl River-Xijiang River economic belt and constructed an evaluation index system for the integration of urban and rural areas in the Pearl River-Xijiang River economic belt from the perspective of production,living,and ecological functions. In addition,the coupling coordination degree model was used to explore the spatial and temporal variation trend of the coupling degree and coupling coordination degree of the production,living,and ecological functions of the urban and rural areas,so as to reveal issues in the integrated development of the urban and rural areas in the study area. The results show that:① In 2005 and 2018,the coupling degree of the production,living,and ecological functions of the urban and rural areas in the Pearl River-Xijiang River economic belt was on the rise,and the spatial distribution was low in the west and high in the east.The coupling degree of production and living functions of the urban and rural areas increased,and that of production and ecological functions changed obviously and reached the coupling phase.② In 2005 and 2018,the coupling coordination degree of production,living,and ecological functions of the urban and rural areas changed slightly,with slightly imbalanced districts and counties as representatives and a planar distribution.The production and living functions of the urban and rural areas were generally improved,while the coupling coordination degree of the living and ecological functions of the areas changed slightly,and it determined the coupling coordination degree of the production,living,and ecological functions.In view of areas with favorable economic conditions,such as Nanning,Liuzhou,Guangzhou,and Foshan,the key to realizing urban and rural integration is to guarantee living conditions and ecological environment and strengthen the coordinated development between urban and rural areas.Furthermore,in view of districts and counties with relatively backward development in the western regions,they need to simultaneously develop the living and ecological functions while developing the production function of urban and rural areas,improve the infrastructure construction in urban and rural areas,and protect the ecological environment,so as to realize integrated development.Finally,the coordinated development of production,living,and ecological functions of urban and rural areas is of great significance to the sustainable development of the region.